Student-faculty Interaction Analysing the Experiences of University Students - Dubey, Alok (JOURNAL OF INDIAN EDUCATION, 2020)
This paper analyses the student-faculty interaction in higher education. The conceptual framework underlying the study is based on the idea of the Student engagement referred as ‘Experience with faculty’ and its two indicators, i.e. ‘interaction with faculty’ and ‘teaching effectiveness’. The study assesses the extent to which students interact with teachers in and outside the classroom and how often they feel that teaching was effective. Data was collected from the sample of 250 students of C.S.J.M. University, Kanpur, Uttar Pradesh, using National Survey of Student Engagement (NSSE) questionnaire followed by an unstructured interview based on the student’s responses. Overall result suggests that a large number of students have minimal contact with faculty and teaching-learning methods are widely teacher-centered.